Injury analysis validation of a deformable vehicle - Venkatason, Kausalyah; Shasthri, Sevaguru; Abdullah, Kassim Abdulrahman; Idres, Moumen; Shah, Qasim Hussain; Wong, Sha Voon (Trans Tech Publications Ltd., Switzerland, 2013)
In the event of an impact with an automobile, pedestrians suffer multiple impacts with the bumper, hood and the windscreen. The characteristics of a vehicle’s front end and structural stiffness have a significant influence on the kinematics and injury risk of the pedestrian’s body regions, in a vehicle-to-pedestrian collision. In this present study, the injury risk of the pedestrian is investigated in an impact with a deformable vehicle front end model for the purpose of validating the developed model. A simplified vehicle front end model consisting of a multi body windscreen and a finite element cowl, hood and bumper is developed. The MADYMO human pedestrian multi body dummy model is impacted by the vehicle front end model at the speed of 40 km/h. The injury to the various body segments namely the head, neck, sternum, lumbar, femur and tibia is obtained. The simulation values are compared to the experimental values for verification of the vehicle front end model.